Establishment of the ecological environmental map for Hoa binh town based on the study of ecological landscape and ecological environment - Thôn, Nguyễn Thế (Vietnam Journal of Earth Sciences, 2018)
Based on the ecolandscape theory and using the Map Info software, the author has established the ecological environmental map for Hoa Binh town. In this map all of natural environmental components, poilution, degradation, catastrophe and break-down of environment are described. Annotation of the map have two parts : 1) the ecolandscape (ecological environment of the territory) is described with matrix ; 2) the pollution, degradation, catastrophe and break-down of environment are described with description table and that is under the matrix.